Like ticking time bombs. Improvising structural competency to 'Defuse' the exploding of violence against emergency care workers in Italy - Mirko Pasquini (Taylor & Francis Group, 2023)
While violence against health care workers is being progressively recognised as a serious problem in the healthcare industry, it remains an under-studied area of enquiry in global public health. Anthropologists have long observed that violence toward patients is tied to institutional care practises in multiple ways, including repression, misrecognition and silencing. But research on health care staff's experience of violence is still lacking. This article aims to address this literature gap by providing research on the daily experience of vulnerability to violence that health care providers face during their work. To do so, the paper ethnographically explores the effects and perception of violence against health care workers in an emergency department (ED) in northern Italy, a place with a dramatic escalation of violent incidents. The article illustrates how the ED staff attended to the experience of suffering of potentially violent patients. In so doing, ED professionals shifted the responsibility of violence against them from violent individuals to violent structures shaping health inequities. The paper thus argues that ED professionals display a structural competence perspective when dealing with violence.